Penegakan Hukum Terhadap Pelaku Pelecehan Seksual Anak Dibawah Umur dalam putusan Nomor 10 / Pid.Sus-Anak / 2019 / PT.Bdg - Alya Tsania Aprillianti; Nandang Sambas (Bandung Conference Series: Law Studies, 2022)
Abstract. Children are the next generation of Indonesia who have r ights and obligations and are development capital that will maintain and sustain the development of the nation. Children’s rights are part of the Human Rights, this contained in the 1945 Constitutuon, which broadly states that Indonesia guarantees and protects the rights of a child from violent and discrimination. Therefore, Law Number 23 of 2014 was made as a form of protection for children. Based on Article 1 Paragraph (2) of Law Number 23 of 2014 stated that child protection is all activities to guarantee and protect children and their rights so that the can live, grow, develop, and participate optimally in accordance with human dignity, and receive protection from violence and discrimination. And in the era of globalization, crimes and violence against children are happening, including sexual crimes, on of which is obscence acts. Crimes and perpertators that arise from acts of obscenity can be said to be quite diverse, and it is undeniable that the perpetrator can also be a child. Currently, cases of sexual harassement are still happening, therefore this study aims to find out how the law is enforces against perpetrators of criminal acts of sexual harassment against minors (Case Study Decision Number 10/Pid.Sus-Anak/2019/PT.Bdg). The application of the law in the case of Decision Number 10/Pid.Sus-Anak/2019/PT.Bdg is based on the Juvenlie Criminal Justice System regulated in Law Number 11 of 2012 because the suspect is a child who is still 17 years old and has the right to grow up and develop as Indonesian’s successor. The regulation of sexual abuse of children in the Criminal Code (KUHP) is general nature, so the Government issued Law Number 23 of 2014 concerning Child Protectino which contains policies on criminal acts of sexual abuse against children and also child protection. Abstrak. Anak merupakan generasi penerus bangsa Indonesia yang mempunyai hak dan kewajiban dan merupakan modal pembangunan yang akan memelihara dan mempertahankan pengembangan bangsa. Hak Asasi Anak merupakan bagian dari Hak Asasi Manusia yang termuat di dalam Undang-Undang Dasar 1945, yang secara garis besar menyatakan bahwa negara menjamin dan melindungi hak seorang anak dari kekerasan diskriminasi. Oleeh karena itu, dibuatlah Undang-Undang Nomor 23 Tahun 2014 sebagai bentuk perlindungan terhadap anak. Dalam Pasal 1 Ayat (2) Undang-Undang Nomor 23 Tahun 2014 menyatakan bahwa perlindungan Anak adalah segala kegiatan untuk menjamin dan melindungi Anak dan hak-haknya agar dapat hidup, tumbuh, berkembang, dan berpartisipasi secara optimal sesuai dengan harkat dan martabat kemanusiaan, serta mendapat perlindungan dari kekerasan dan diskriminasi. Dan era globalisasi yang terus maju dan berkembang, kejahatan maupun kekerasan yang menimpa anak marak terjadi, tidak terkecuali dengan kejahatan seksual yang salah satunya adalah tindak pencabulan. Kejahatan dan pelaku yang timbul dari tindak pencabulan pun bisa dibilang cukup beragam, dan tidak dapat dipungkiri pelaku pun dapat merupakan seorang anak. Saat ini, kasus peleccehan seksual pun masih marak terjadi, maka dari itu penelitian ini bertujuan untuk mengetahui bagaimana penegakan hukum terhadap pelaku tindak pidana pelecehan seksual terhadap anak dibawah umur (Studi Kasus Putusan Nomor 10/Pid.Sus-Anak/2019/PT.Bdg). Penerapan hukum dalam kasus Putusan Nomor 10/Pid.Sus-Anak/2019/PT.Bdg didasarkan pada Sistem Peradilan Pidana Anak yang diatur dalam Undang-Undang Nomor 11 Tahun 2012 karena Tersangka merupakan seorang anak yang masih berumur 17 tahun